Emergency roentgen-endovascular clot aspiration in cardioembolic stroke - S. A. Atamanov; A. V. Mel’nik; A. I. Kvashin; I. V. Korobeinikov; T. G. Grigoryev (Бюллетень сибирской медицины)
A case report of successful intravascular aspiration in a patient with acute cardioembolic stroke is presented. Non-occlusive critical thrombosis of the extracranial segment of the left internal carotid artery with distal total embolization of the medial cerebral artery was verified. During the intervention, the dislocation of thrombotic masses into the supraclinoid segment occurred.